2016
DOI: 10.1080/13880209.2016.1223146
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolates profile, volatile constituents, antimicrobial, and cytotoxic activities of Lobularia libyca

Abstract: Context: Brassicaceae plants are associated with protection against cancers due to their glucosinolate contents. Objectives: We investigate fresh leaves, roots and ripe seeds of Lobularia libyca (Viv.) C.F.W. Meissn. (Brassicaceae) to identify their glucosinolate constituents, antimicrobial and cytotoxic activities Materials and methods: The glucosinolates were identified using GC-MS analysis of their hydrolysis products and LC-MS analysis in the case of seeds. Disc diffusion (1 mg/disc) and minimum inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…aeruginosa . It was shown that seed hydrolysates have significant activity against both tested microorganisms [46]. …”
Section: Active Compounds Of Plants With Antimicrobial Propertiesmentioning
confidence: 99%
“…aeruginosa . It was shown that seed hydrolysates have significant activity against both tested microorganisms [46]. …”
Section: Active Compounds Of Plants With Antimicrobial Propertiesmentioning
confidence: 99%
“…The calculation of IC 50 values was performed using GraphPad Prism software version 7.0. The criteria used to categorize the activity against the tested cell lines was based on IC 50 values as follows: 20 µg/mL = highly active, 21 to 200 µg/mL = moderately active, 201 to 500 µg/mL = weakly active, and >501 µg/mL = inactive [20].…”
Section: Cell Viability Assay (Mtt)mentioning
confidence: 99%
“…Lobularia arabica methanolic extract was the least effective in AFB control and on the population parameters of the Carniolan honey bees among the three herbal extracts. Al-Gendy et al (2016) identified three glucosinolates from the genus Lobularia lybica with antimicrobial and cytotoxic activities.…”
Section: Discussionmentioning
confidence: 99%